Phenological diversity of maprounea guianensis (euphorbiaceae) in humid and dry neotropical forests - Dos Santos, Marília G. M.; Neves, Sâmia P. S.; Do Couto-Santos, Ana P. L.; Cerqueira, Carlianne O.; Rossatto, Davi R. [UNESP]; De Miranda, Lia D. P.; Funch, Ligia S. (CSIRO Publishing, 2020)
Phenological diversity, seasonality and leaf longevity may affect leaf habits, reflecting plant responses to environmental conditions. Maprounea guianensis Aubl. is a widespread species in Brazil that is associated with different forest types. We investigated how phenological diversity, seasonality and leaf longevity affect leaf habits of its populations growing in humid and dry forests in the Chapada Diamantina mountains. We made monthly observations of leaf budding and fall in 62 individual trees between 2004 and 2012 (84 months), estimating leaf longevity based on phenophase evaluations. We made use of circular statistics, cross correlations and the Shannon-Wiener Index to evaluate our data. There was little variation in rainfall distribution between the study years, although water availability differed at each site. Phenophase seasonality was found to be negatively correlated with rainfall but positively correlated with photoperiod. Low phenological diversity was observed within each site, but not between sites, and leaf longevity was reduced in the dry forest. Although macroclimatic conditions were similar throughout the range of occurrence of M. guianensis in the region, we found that phenological behaviour and leaf longevity differed according to micro-site differences, demonstrating the plasticity of the species, which may favour its occupation of different environments.
Keywords: drought; intraspecific variation; photoperiod; water relations